2022
DOI: 10.2147/nss.s378564
|View full text |Cite
|
Sign up to set email alerts
|

Association of Dietary Behaviors with Poor Sleep Quality and Increased Risk of Obstructive Sleep Apnea in Korean Military Service Members

Abstract: Purpose Sleep quality among military service members is important for enhancing their capabilities and preventing psychiatric problems. We aimed to explore the association of dietary behaviors with poor sleep quality and increased risk of obstructive sleep apnea (OSA) in military men on active duty. Patients and Methods A large-scale multi-site cross-sectional survey was conducted in five units of the Republic of Korea’s army. Poor sleep quality and increased risk of OS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 61 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Studies across the countries explored the correlation between sleep quality and breakfast skipping, shedding light on how the factors interplay in various population groups [ 43 46 ]. This study strengthens the evidence by showing that university students who reported poor sleep quality were three times more likely to skip breakfast than their counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies across the countries explored the correlation between sleep quality and breakfast skipping, shedding light on how the factors interplay in various population groups [ 43 46 ]. This study strengthens the evidence by showing that university students who reported poor sleep quality were three times more likely to skip breakfast than their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…This study strengthens the evidence by showing that university students who reported poor sleep quality were three times more likely to skip breakfast than their counterparts. The critical aspect of this connect is that sleep is linked to circadian rhythms, hormone regulation, and overall metabolic health, which in turn affect dietary habits [ 43 – 45 , 47 ]. Students are often stressed with academic works, irregular schedules, and cultural activities, disrupting their sleep patterns, leading to poor sleep quality among them [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, only evening eating and night eating were significantly associated with sleep quality. Similarly, the frequency of snacking and irregularity of night eating among Korean military service members were associated with poor sleep quality (Choi et al 2022). In another study, late dinner was positively associated with poor sleep quality (Lopes et al 2019).…”
Section: Association Between Sleep Quality and Chrononutrition Behaviorsmentioning
confidence: 94%
“…Other studies in the literature did not contemplate the association of sleep quality in officers. 7,35 Compared with soldiers, officers do not perform the same services in shifts, in addition to having a higher education level and salary, which can improve sleep in these individuals. 37 Furthermore, our study includes officers in a single category, not differentiating according to their rank due to statistical representativeness; As a result, even though they are officers, there are a large number of military personnel with low ranks in the officer corps who do not have a command function; this can alter health aspects such as less stress, less responsibility at work and even family issues, such as not having children.…”
Section: Protective Factorsmentioning
confidence: 99%
“…This can culminate in a high prevalence of poor sleep quality among these professionals. 7 This inadequacy can induce negative physiological and behavioral effects, increase reaction time, and worsen performance in visuospatial tasks 8 increasing the chances of errors and accidents. It can also impact physical performance, aggravate injuries, generate cognitive impairment, and interfere with leadership, and the ability to make decisions and carry out planning.…”
Section: Introductionmentioning
confidence: 99%